Effect of Strain Rate on the Deformation Characteristic of AlN Ceramics under Scratching - Shang Gao; Honggang Li; Renke Kang; Yu Zhang; Zhigang Dong (Micromachines, 2021)
To clarify the influence mechanism of strain rate effect on deformation characteristics of aluminum nitride (AlN) ceramics, some varied-velocity nanoscratching tests were carried out using a Berkovich indenter in this paper. The deformation characteristics of the scratched grooves were observed using the scanning electron microscope. The experimental results showed higher scratch speed would lead to shallower penetration depth, fewer cracks, and indenter fewer slipping, which was more conducive to the plastic deformation of AlN ceramics. Considering the strain rate effect and the elastic recovery of material, a model for predicting the Berkovich indenter penetration depth under edge-forward mode was established. The prediction results were consistent with the experimental data, and the error was less than 5%, indicating that the model is effective. Based on the Boussinesq field, the Cerruti field, and the Sliding bubble field, a strain rate dependent scratch stress field model was established. The stress field revealed higher scratch speed may significantly reduce the maximum principal stress in the stress field under the indenter, which is the fundamental reason for reducing the crack damage and promoting the plastic deformation. The above study can provide theoretical guidance for reducing the processing damage of AlN ceramics.